Pembentukkan Karakter Anak Usia Dini Melalui Keterampilan Seni Mendongeng - Engel Bertha Halena Gena; I Made Sutama; I Putu Mas Dewantara; Kadek Wirahyuni (Prodi. Manajemen Pendidikan Islam, Fakultas Tarbiyah, Institut Pesantren Sunan Drajat, 2025)
The purpose of this study is to describe the art of storytelling skills in Early Childhood as a medium of education and entertainment, in shaping children's personalities, and guiding children's emotional intelligence. Character formation from an early age is very important so that children have a strong mentality when facing challenges, changes and certain situations in the future. The problems that are currently spreading in national life are the moral crisis and the crisis of role models. The moral crisis can be overcome through character building. In the scope of schools, character building can be applied through learning literature that has a moral dimension. We can say that the main function of children's literature is delce et utite 'to entertain and educate', which in practice are interconnected. Children's literature can play a role as an effective character builder because the moral values ​​(honesty, sacrifice, democracy, politeness, love, justice, and friendship) it carries are conveyed implicitly. The message of the story can be realized metaphorically so that the teaching and learning process takes place pleasantly and does not patronize. Instilling commendable characters in early childhood through fairy tales can be said to be the most effective because fairy tales are so close to their daily lives. The goal of literature education in Elementary Schools through fairy tales is in line with the goal of national education, namely the formation of humans who have good understanding, attitudes, and behavior. This research is a type of descriptive literature study. The sample in this study is a sample of the prose genre taken from local Sumbanese wisdom which is generally known by children such as Folk tales or fairy tales such as Watu Maladong, Wee Wini, Watu Kaweda and Pasola. Data collection techniques use library data collection methods, reading and recording, and processing research materials